Feeding Two Birds with One Scone: Using AWE to Enhance Writing and Creativity among Pre-university Students - Norhazwanie, Jatin; Hafizoah, Kassim; Nor Yazi, Khamis; Asiah, Kassim (IEEE Xplore, 2023)
The artificial intelligence (AI) revolution has redefined the practices of teaching and learning writing in academia. AI tools being so accessible to students appear to have desirable effects for self-learning, yet they are also capable of veering them off course. This paper is a pilot study to reveal the potency of employing Automated Writing Evaluation (AWE), an AI-based tool with the application of natural language processing (NLP) to analyse and generate feedback on various aspects of writing in English language writing instructions to improve writing proficiency and creative performance. Pre-test for writing and creativity were administered to eleven CEFR B1 second language learners. Upon using an AWE tool as formative assessment, post-tests and interview protocol were conducted to obtain a richer analysis of the data. The results indicate improvements in writing and creativity scores. The participants believed that the use of AWE particularly improved their writing proficiency due to these features: unlimited revision, interactivity, immediate feedback. This study serves as a springboard for writing teachers to incorporating AI tools in their writing lessons while acknowledging the potential of creativity to be stimulated in those lessons.